DAKWAH POLITIK ISLAM ABDURRAHMAN WAHID DI ERA REFORMASI - Khotimah (Penerbit CV Tentrem Karya Nusa, 2018)
Ulama politics has a different pattern from the politics of statesmen, intellectuals an cultural observers because the ulama politics is actually based on the element of da'wah or the term is